Ziarah dan Relasi Sunni-Syiah: Akar Serazngan Mematikan Terhadap Peziarah di Pakistan - Muhammad Tarobin (Hikmah: Journal of Islamic Studies, 2019)
One of the areas that had conflict and the deadliest religious conflicts and violence in Islam world is in Pakistan, a Nation that has strong and profound Islamic tradition. Muslims in Pakistan are around 180 millions population, and 15 percent among them are followers of Shia madzhab. It has been three decades since Pakistan was declared in 17 August 1947, Sunni and Shia community lived in Harmony. However, ahead of Islamic revolution in Iran in 1979, Sunni-Shia’s relation heated up. In the last two decades, Pakistan region has become the deadliest region, especially for Pakistan Shia Pilgrims. This paper tries to see the root of the problems. Based on study toward literary materials, there are three factors causing Sunni-Shia conflict in Pakistan, which are : by the appointment of General Muhammad Zia-ul-Haq in the authority (1977), The Iranian Islamic Revolution in 1979, and the politics of nerve war in border Kashmir and Afganistan. Nevertheles, conflicts and the deadly violence are more complex due to power competition in the country and intervention from United States, Saudi Arabia, and Iran. Keywords: Wali, Tawassul bi al-Dhāt, Salafi- Wahabi, Imāmiyah. Salah satu wilayah yang mengalami konflik dan kekerasan keagamaan paling mematikan di dunia Islam adalah Pakistan, negara yang memiliki tradisi keIslaman cukup kuat dan mengakar. Umat Muslim di Pakistan berjumlah sekitar 180 juta, dan 15 persen diantaranya merupakan penganut mazhab Syiah. Telah tiga dasawarsa sejak Pakistan didirikan pada 17 Agustus 1947, komunitas Sunni dan Syiah hidup dalam suasana harmonis. Namun menjelang revolusi Islam di Iran pada 1979, hubungan Sunni- Syiah memanas. Dua dasawarsa terakhir wilayah Pakistan menjadi wilayah paling mematikan, khususnya bagi peziarahpeziarah Syiah Pakistan. Tulisan ini hendak melihat akar permasalahan tersebut. Berdasarkan telaah terhadap bahanbahan tertulis, ada tiga faktor yang menyulut konflik Sunni- Syiah di Pakistan, yakni: naiknya Jenderal Muhammad Zia-ul- Haq dalam tampuk kekuasaan (tahun 1977), Revolusi Islam Iran tahun 1979, dan politik perang syaraf di perbatasan Kashmir dan Afghanistan. Namun, konflik dan kekerasan mematikan tersebut semakin kompleks akibat persaingan kekuasaan di dalam negeri, dan campur tangan Amerika Serikat, Saudi Arabia, dan Iran. Kata Kunci: Wali, Tawassul bi al-Dhāt, Salafi- Wahabi, Imāmiyah.